Role of Vitamin C in Health and Disease: A Comprehensive Review (Advances in Applied Biological Research, 2025)
Vitamin C (ascorbic acid) is a water-soluble vitamin with vital roles in human  health. It functions as a potent antioxidant, supports the immune system, aids  in collagen synthesis, and enhances iron absorption. The deficiency of vitamin  C leads to scurvy, while its adequate intake is associated with numerous health  benefits, including reduced risk of chronic diseases such as cardiovascular disease,  cancer, and neurodegenerative disorders. Supplementation with vitamin C  appears to be able to both prevent and treat respiratory and systemic infections.  This review provides an analysis of the role of vitamin C in health and disease, its  dietary sources, recommended intake, and its therapeutic applications based on  recent literature.
Keywords: Vitamin C; Health benefits; Dietary sources